The Administration of Probiotics to Prevent Diarrhea in Cervical Cancer Patients Undergoing Radiotherapy: A Literature Review - Dewi Wulandari; Tarafainy Basalamah; Diyah Eka Andayani (Indonesian Journal of Cancer, 2023)
Background: Cervical cancer is the 4th most prevalent among women worldwide and ranks as the 4th leading cause of cancer-related death. During radiotherapy for this disease, about 80% of patients experience diarrhea or radiation-induced diarrhea (RID) which can significantly compromise quality of life and disrupt the continuity of the therapy when left untreated. Furthermore, it was reported that probiotics exhibit promising efficacy in preventing the incidence of RID, but the conclusive nature of this investigation remains uncertain. This study aimed to determine the effectiveness of probiotics in preventing the incidence of diarrhea in cervical cancer patients receiving radiotherapy.Methods: A comprehensive search was conducted on 4 large databases, namely Pubmed, PMC, Cochrane Library, and EMBASE, adhering to the eligibility criteria. Results: Following the application of the stipulated eligibility criteria, 2 articles were obtained, namely Systematic Reviews/Metaanalysis (SR/MA) and Randomized Control Trial (RCT). The risk ratio of diarrhea incidence in cervical cancer patients who were administered probiotics while receiving radiotherapy was 0.61 (CI 95% 0.46-0.81, p=0.0007). The therapeutic effect was most pronounced when Lactobacillus acidophilus and Bifidobacterial strains, were given 3 times daily. Conclusions: The administration of probiotics proved to be a valuable strategy in preventing the incidence of diarrhea in cervical cancer patients receiving radiotherapy